Pancreatic neuroendocrine tumor mimicking intraductal papillary mucinous neoplasm: Case report - AKMERCAN, AHMET; BAĞCI ÇULÇİ, PELİN; ATICI, ALİ EMRE; YEGEN, ŞEVKET CUMHUR; UPRAK, TEVFİK KIVILCIM (My University, 2021)
ABSTRACTPancreatic neuroendocrine tumors (PanNETs) are rare pancreatic tumors. They usually exhibit parenchymal growing, however some cases can exhibit intraductal growing. PanNET with intraductal growth may cause intraductal papillary mucinous neoplasm (IPMN)- like clinic scenario by presenting as cystic formations secondary to duct obstruction. In our case, a 69-year- old man with a history of abdominal pain and nausea underwent a computed tomography scan that showed dilated pancreatic duct and cystic lesion which was 8 cm originating from the pancreas. Imaging and laboratory findings were considered to be consistent with an IPMN so the patient underwent distal pancreatectomy and splenectomy. However, the pathological examination of the surgical specimen showed a millimeter-sized PanNET located in pancreatic tail mimicking the IPMN by obstructing the pancreatic duct.Keywords: Gastroenteropancreatic neuroendocrine tumor; pancreatic intraductal neoplasms
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Genel Cerrahi; Cerrahi Onkoloji; Medicine; Health Sciences; Surgery Medicine Sciences; General Surgery; Surgical Oncology; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Surgery; Gastroenteropancreatic neuroendocrine tumor; pancreatic intraductal neoplasms